Kesamaan Elektromiogram pada Otot yang Memiliki Morfologi Mirip - Tomas Marcelino A. Martin; Abdurachman Abdurachman; Subagyo Subagyo; Irfiansyah Irwadi (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Introduction: Muscles are the largest tissue group in the body and can be classified into various classifications, one of which is based on their morphological shape. Examination of muscles, especially skeletal muscles, can use electromyography. The purpose of this study was to determine whether muscles that have similar morphology have no different electromyogram.Method: This is a descriptive observational study using needle electromyography. The sample amounted to 5 with five times MUP (Motor Unit Potential) in each musculus deltoideus and musculusResult: The mean amplitude, duration, number of voltage phases and the number of voltage turns off the musculus deltoideus and musculus gluteus medius in the study subjects were similar (p-value greater than 0.05).Conclusion: Muscles that have similar morphology in each parameter of amplitude, duration, number of voltage phases, and number of voltage turns do not have a significant difference in electromyogram.